Experimental method for rapidly preparing copper oxide nanowire and application thereof
Through constant voltage anodization and high-temperature heat treatment, CuxO nanowire arrays are quickly prepared, which solves the problem of inconsistent nanowire structures during the anodizing process of copper mesh, improves the specific surface area and photoelectric performance of nanowires, and realizes industrial production. feasibility.
Patent Information
- Application Number
- CN202411544948.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-11-01
AI Technical Summary
During the copper mesh anodization process, due to errors in the surface area of the material, the surface current deviation is caused, which makes it difficult for the nanowire structure to remain consistent.
Cu(OH)2 nanowire arrays were quickly prepared on the surface of copper mesh using constant voltage anodization method, and dehydrated through high-temperature heat treatment to prepare CuxO nanowire arrays in situ.
It solves the problem of inconsistent nanowire structures, improves the specific surface area and photoelectric performance of nanowires, simplifies the preparation process, reduces costs, and is suitable for industrial production.
Smart Images

Figure CN119349624A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of photoelectrocatalytic material preparation and the photoelectrochemical technology of energy and environment, and in particular to an experimental method for rapidly preparing copper oxide nanowires and an application thereof. Background Art
[0002] With the continuous growth of global energy demand and the gradual depletion of oil resources, solar energy has great potential as an inexhaustible clean energy source, and hydrogen energy, as an important clean energy source, has become a hot topic of research through photolysis of water and photoelectrochemical decomposition of water. Ideally, the Fermi level of the semiconductor in the photoelectrochemical water splitting cell is balanced with the redox potential of the electrolyte solution, resulting in band bending and thus generating an electric field. In terms of hydrogen production, p-type semiconductors have advantages over n-type semiconductors. On p-type semiconductors, electrons can be directly injected into the electrolyte, thereby directly reducing water to hydrogen at the interface of the p-type semiconductor. On n-type semiconductors, photogenerated electrons must migrate through an external circuit before they can be used for water reduction on the counter electrode, which involves potential energy losses. As the importance of p-type oxide semiconductors in the field of energy materials becomes increasingly prominent, the number of p-type oxides available is very scarce compared to n-type oxides. As a representative p-type oxide, copper oxide has attracted widespread attention in different research fields. In addition, one-dimensional nanostructures (such as nanowires, nanorods, and nanotubes) have become a promising solution to the mismatch between short carrier diffusion length and long light absorption depth common in many semiconductors because they can independently adjust the actual carrier diffusion length and light absorption depth of semiconductors. Due to the unique optoelectronic properties of nanowire structures, especially in charge transport, they have become an important component of nanodevices and integrated nanosystems, and play an important role in catalysis and energy-related fields.
[0003] Copper oxide (CuO), as a p-type semiconductor with a narrow band gap (≤1.2 eV) and the cornerstone of high-temperature superconductors and giant magnetoresistance materials, has always been a hot topic in the study of transition metal oxides. CuO nanowires have a large surface area and potential size effect, exhibiting superior physical and chemical properties that are significantly different from their micron or bulk counterparts. Cuprous oxide (Cu2O) is also generally considered to be a material with a suitable bandgap width (approximately 2.0~2.2 eV) and high carrier conductivity and mobility. Its specific physical and chemical properties largely depend on the corresponding preparation methods. As a representative intrinsic p-type inorganic semiconductor material, Cu2O has been widely used in photovoltaics, catalysis, chemical industry and other fields. Copper oxide (Cu xO) can be synthesized by a variety of methods, including thermal oxidation, thermal reduction, chemical vapor deposition, electrochemical deposition, hydrothermal method, solvent reduction method, magnetron sputtering and pulsed laser deposition. In terms of production technology, the constant voltage anodizing method is simple and fast to operate. It does not require accurate calculation of the surface area of the workpiece, but only requires setting the voltage and time, which helps to reduce production costs. The thermal oxidation method is the simplest and fastest synthesis method. Metallic copper is used as the raw material. Copper can be oxidized to Cu2O in an oxygen-free environment and to CuO in an aerobic environment.
[0004] In the preparation process, the method of anodic oxidation and high temperature heat treatment is combined to quickly obtain Cu on the surface of the copper mesh. x O nanowire arrays. This nanowire array structure not only increases the specific surface area, but also helps to increase the light contact area in optoelectronic applications. The constant voltage anodization method effectively ensures the structural consistency of the nanowires. The in-situ growth optimizes the contact between the nanowires and the substrate, avoids the need for additional conductive agents and adhesives, and improves the overall performance of the battery. In summary, this study can not only provide an experimental method for the rapid preparation of copper oxide nanowires, but also the preparation of Cu x The process of O nanowires is simple and efficient. The application of materials provides important technical support for promoting energy transformation and environmental protection, and can effectively alleviate the global energy crisis and environmental pollution problems. Summary of the invention
[0005] The purpose of this section is to summarize some aspects of the embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0006] In view of the above and / or existing problems in the preparation of existing photoelectrocatalytic materials and the photoelectrochemistry of energy and environment, the present invention is proposed.
[0007] Therefore, the purpose of the present invention is to solve the problem that the surface current deviation caused by the error in the surface area of the material during the anodization of the copper mesh leads to the difficulty in maintaining the consistency of the structure of the nanowire, and to provide an experimental method for quickly preparing copper oxide nanowires and its application. The experimental method is simple and controllable. The constant voltage anodization method can be used to quickly and stably prepare nanowires without calculating the surface current of the material. The copper hydroxide (Cu(OH)2) is in situ dehydrated / thermally decomposed into copper oxide (Cu x O), which is beneficial to Cu without changing the nanostructure x Rapid preparation of O nanowire materials, and the prepared Cu xO nanowire materials are mainly used in the field of photoelectric water decomposition to produce hydrogen and light-assisted Li-CO2 batteries and have good photoelectric properties. x O nanowire materials are conducive to the separation of photogenerated electrons and holes, effectively solving the problem of low light energy utilization.
[0008] To achieve the above object, the present invention adopts the following technical solutions:
[0009] An experimental method for rapidly preparing copper oxide nanowires and its application, characterized in that it comprises the following steps: Step 1: Using deionized water as solvent, adding KOH and continuously stirring to obtain an electrolyte for an anodic oxidation reaction, and introducing dry nitrogen to deoxygenate the electrolyte; Step 2: Cut out copper meshes and copper sheets of the same size, first degrease them in a mixed solution of NaOH and NaHCO3 for about 5 minutes, then prepare a polishing solution to polish the degreased copper meshes and copper sheets for about 20 to 30 seconds, and then place them in a water washing solution for ultrasonic washing for about 10 minutes, and then use a compressed air flow to dry the copper meshes and copper sheets to remove organic pollutants and oxide layers on the surfaces of the copper meshes and copper sheets; Step 3: In the electrochemical reaction device of the double-electrode system, a copper mesh and a copper sheet are used as the anode and cathode, respectively. The copper mesh is electrochemically anodized at a constant voltage, and the temperature range of the electrochemical reaction device is controlled between 20 and 30°C using a rotary evaporation table. A Cu(OH)2 nanowire array is quickly prepared on the surface of the copper mesh. The Cu(OH)2 mesh after constant voltage anodization is rinsed with deionized water and then dried using a compressed air stream; Step 4: Place the Cu(OH)2 mesh vertically in a quartz crucible in a tube furnace and perform heat treatment under an argon atmosphere. After high temperature annealing, the Cu x O nanowires; Step 5: Prepare a test solution of Na2SO4 with a concentration of 0.1 mol / L, deoxygenate the solution with dry nitrogen, and x O mesh was used as the working electrode, Pt sheet as the counter electrode, and AgCl electrode as the reference electrode. The photoelectrochemical properties of the materials were tested under xenon lamp irradiation. The Cu with the largest photocurrent was selected. x O network is used in photolysis of water to produce hydrogen and light-assisted Li-CO2 battery.
[0010] As an experimental method for rapidly preparing copper oxide nanowires and further improvements in its application, the invention comprises:
[0011] Preferably, the electrolyte for the anodic oxidation reaction in step 1 is a KOH solution with a concentration of 2 mol / L, and dry nitrogen is bubbled into it for at least 30 minutes.
[0012] Preferably, the mixed solution for degreasing treatment in step 2 is a mixed solution of NaOH and NaHCO3 with a concentration of 1 mol / L, the configuration ratio of the polishing solution is HF:HNO3:H2O=1:4:5 (vol%), and the configuration ratio of the water washing solution is C2H5OH:C3H6O:H2O=1:1:10 (vol%).
[0013] Preferably, in step 3, the voltage range of the electrochemical anodization treatment of the copper mesh under constant voltage is 1.2-1.7 V, and the reaction time is 200-1200 seconds.
[0014] Preferably, the temperature of the heat treatment in the argon atmosphere in step 4 is 200-600° C., the heating rate is 2° C. / min, and the holding time is 2 hours.
[0015] Preferably, in step 5, Cu x O nanowire materials in the application of photolysis of water to produce hydrogen, using H-type electrolyzer to collect hydrogen and oxygen, Cu x O mesh was used as the working electrode, Pt sheet as the counter electrode, AgCl electrode as the reference electrode, and an external voltage between -0.6 V and -0.8 V was applied under xenon lamp irradiation. x O nanowire material to produce hydrogen on one side; Application in light-assisted Li-CO2 battery, Cu x O mesh is used as the positive electrode material, Li sheet is used as the negative electrode, and 1cm is reserved for the positive electrode shell of the battery. 2 The circular hole allows the xenon lamp to directly illuminate the Cu x O material surface, the Li-CO2 battery as a whole was placed in a closed gas chamber of 0.03MPa pure CO2 for testing.
[0016] Compared with the prior art, the present invention has the following beneficial effects:
[0017] (1) The Cu(OH)2 nanowire array was quickly prepared on the surface of the copper mesh by a constant voltage anodization method, and then the Cu(OH)2 was rapidly dehydrated by high temperature heat treatment to prepare the Cu(OH)2 nanowire array in situ. x The O nanowire array solves the problem that the surface area error of the material leads to the deviation of the surface current during the anodization of the copper mesh, which makes it difficult to maintain the consistent structure of the nanowires. The morphological characteristics are better than the nanowires currently prepared by constant current anodization. This method can complete the anodization of a larger area of material. The preparation process is simple and convenient, and the preparation cost is low, which is conducive to industrial production.
[0018] (2) The present invention uses a copper mesh to prepare Cu x O substrate, Cu was prepared by anodic oxidation and high temperature heat treatment xO nanowire arrays, because each copper wire has a cylindrical three-dimensional structure, have better performance than Cu prepared from traditional copper sheets and copper foils. x O nanowires have a higher specific surface area, which allows more nanowires to be grown on a limited substrate space and helps to expose them to more light in optoelectronic testing and applications.
[0019] (3) Prepared Cu x Copper oxide nanowire materials have a wide visible light absorption range as photoelectrocatalytic materials, and have good performance in the fields of photodecomposition of water to produce hydrogen and light-assisted Li-CO2 batteries. Copper oxide nanowire materials are conducive to the separation of photogenerated electrons and hole pairs, thus solving the problem of low light energy utilization of photoelectrocatalytic materials. In addition, this in-situ growth technology helps to maintain good contact and adhesion between the nanowires and the substrate. The copper mesh substrate is used as a current collector without the need for additional conductive agents and adhesives, which can ensure relatively excellent battery performance. As a positive electrode material for Li-CO2 batteries, the test results show that the charge and discharge voltage is close to the theoretical value. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the present invention will be described in detail below in combination with the accompanying drawings and detailed embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0021] Figure 1 The flowchart of the experimental method for rapidly preparing copper oxide nanowires of the present invention.
[0022] Figure 2 The optical microscope images (sub-image) and scanning electron microscope images (main image) of the Cu(OH)2 nanowire material prepared at 1.2V (a), 1.3V (b), 1.4V (c), 1.5V (d), 1.6V (e), and 1.7V (f) in Example 1 of the present invention are shown in Figure 1, where the scanning electron microscope was taken at a magnification of 25000×. Figure 2 g. Figure 2 h. Figure 2 i, corresponding to Figure 2 d. Figure 2 e. Figure 2 f Cu(OH)2 nanowire material photographed at a magnification of 10000×.
[0023] Figure 3Optical microscope images (sub-image) and scanning electron microscope images (main image) of the Cu(OH)2 nanowire material prepared under the conditions of 200 seconds (a), 400 seconds (b), 600 seconds (c), 800 seconds (d), 1000 seconds (e), and 1200 seconds (f) in Example 2 of the present invention.
[0024] Figure 4 The Cu prepared at 200°C (a), 300°C (b), 400°C (c), 500°C (d), 550°C (e), and 600°C (f) in Example 3 of the present invention is x Optical microscope image (sub-image) and scanning electron microscope image (main image) of O nanowire material, where the scanning electron microscope was taken at a magnification of 25000× Figure 2 g. Figure 2 h. Figure 2 i, corresponding to Figure 2 d. Figure 2 e. Figure 2 f Cu(OH)2 nanowire material photographed at a magnification of 10000×.
[0025] Figure 5 The Raman curves (a) and X-ray diffraction curves (b) of the Cu(OH)2 nanowire material prepared under different anodizing voltage conditions in Example 1 of the present invention, the Raman curves (c) and X-ray diffraction curves (d) of the Cu(OH)2 nanowire material prepared under different anodizing time conditions in Example 2 of the present invention, and the Raman curves (c) and X-ray diffraction curves (d) of the Cu(OH)2 nanowire material prepared under different annealing temperatures in Example 3 of the present invention. x Raman curve (e) and X-ray diffraction curve (f) of O nanowire material.
[0026] Figure 6 The photoelectrochemical test and application test diagram in Example 4 of the present invention includes: Cu x O nanowire material photocurrent curve (a), UV-visible absorption curve (b), Tauc curve (c), Mott-Schottky curve (d), Cu under light conditions x Energy band diagram of O nanowires (e), hydrogen production effect diagram (f), photocurrent and dark current curves of light-assisted Li-CO2 batteries (g) and charge and discharge cycle curves (h). DETAILED DESCRIPTION
[0027] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. The present invention will be described in more detail below through specific examples, but the scope of protection of the present invention is not limited to these embodiments.
[0028] Example 1
[0029] This embodiment provides an experimental method for rapidly preparing copper hydroxide nanowires by controlling anodization voltage, which specifically includes the following steps: Step 1: Using deionized water as solvent, prepare a KOH solution with a concentration of 2 mol / L, and use it as the electrolyte for the anodic oxidation reaction after continuous stirring. Bubble dry nitrogen for at least 30 minutes to deoxygenate the electrolyte. Step 2: Cut out the copper mesh and copper sheet of size 2cm×3cm, first degrease in a mixed solution of NaOH and NaHCO3 with a concentration of 1mol / L for about 5 minutes, then prepare a polishing liquid with a ratio of HF:HNO3:H2O=1:4:5 (vol%) to polish the degreased copper mesh and copper sheet for about 20-30 seconds, and then place them in a water washing liquid with a ratio of C2H5OH:C3H6O:H2O=1:1:10 (vol%) for ultrasonic washing for about 10 minutes, and then use compressed air flow to dry the copper mesh and copper sheet to remove organic pollutants and oxide layers on the surface of the copper mesh and copper sheet; Step 3: In the electrochemical reaction device of the double-electrode system, a copper mesh and a copper sheet are used as the anode and cathode, respectively. The copper mesh is electrochemically anodized at a constant voltage, the voltage range of the anodization is 1.2~1.7V, the anodization time is 600 seconds, and the temperature range of the electrochemical reaction device is controlled between 20~30°C using a rotary evaporator. A Cu(OH)2 nanowire array is quickly prepared on the surface of the copper mesh. The Cu(OH)2 mesh after constant voltage anodization is rinsed with deionized water and dried using a compressed air stream.
[0030] Figure 2 The optical microscope images (sub-image) and scanning electron microscope images (main image) of the Cu(OH)2 nanowire material prepared at 1.2V (a), 1.3V (b), 1.4V (c), 1.5V (d), 1.6V (e), and 1.7V (f) in Example 1 of the present invention are shown in Figure 1, where the scanning electron microscope was taken at a magnification of 25000×. Figure 2 g. Figure 2 h. Figure 2 i, corresponding to Figure 2 d. Figure 2 e. Figure 2 f Cu(OH)2 nanowire material photographed at a magnification of 10000×. Comparing the experimental conditions of different anodization voltages, the Cu(OH)2 nanowires prepared at a voltage of 1.4V have complete tips, and each one is relatively long and densely distributed. Figure 5The Raman curves (a) and X-ray diffraction curves (b) of the Cu(OH)2 nanowire material prepared under different anodization voltage conditions in Example 3 of the present invention show the characteristic peaks of the Cu(OH)2 material, and the peak value of the characteristic peak of the sample with a voltage of 1.4 V is the highest.
[0031] Example 2
[0032] This embodiment provides an experimental method for rapidly preparing copper hydroxide nanowires by controlling the anodic oxidation time, which specifically includes the following steps: Step 1: Using deionized water as solvent, prepare a KOH solution with a concentration of 2 mol / L, and use it as the electrolyte for the anodic oxidation reaction after continuous stirring. Bubble dry nitrogen for at least 30 minutes to deoxygenate the electrolyte. Step 2: Cut out the copper mesh and copper sheet of size 2cm×3cm, first degrease in a mixed solution of NaOH and NaHCO3 with a concentration of 1mol / L for about 5 minutes, then prepare a polishing liquid with a ratio of HF:HNO3:H2O=1:4:5 (vol%) to polish the degreased copper mesh and copper sheet for about 20-30 seconds, and then place them in a water washing liquid with a ratio of C2H5OH:C3H6O:H2O=1:1:10 (vol%) for ultrasonic washing for about 10 minutes, and then use compressed air flow to dry the copper mesh and copper sheet to remove organic pollutants and oxide layers on the surface of the copper mesh and copper sheet; Step 3: In the electrochemical reaction device of the double-electrode system, a copper mesh and a copper sheet are used as the anode and cathode, respectively. The copper mesh is electrochemically anodized at a constant voltage, the anodization time is 200-1200 seconds, the anodization voltage is 1.4V, and the temperature range of the electrochemical reaction device is controlled between 20 and 30°C using a rotary evaporator. A Cu(OH)2 nanowire array is quickly prepared on the surface of the copper mesh. The Cu(OH)2 mesh after constant voltage anodization is rinsed with deionized water and dried using a compressed air stream.
[0033] Figure 3 The optical microscope images (sub-image) and scanning electron microscope images (main image) of the Cu(OH)2 nanowire material prepared under the conditions of 200 seconds (a), 400 seconds (b), 600 seconds (c), 800 seconds (d), 1000 seconds (e), and 1200 seconds (f) in Example 2 of the present invention. Comparing the experimental conditions of different anodization times, the Cu(OH)2 nanowires prepared at a time of 800s have complete tips, are relatively long, and are densely distributed. Figure 5 The Raman curve (c) and X-ray diffraction curve (d) of the Cu(OH)2 nanowire material prepared under different anodizing time conditions in Example 2 of the present invention show the characteristic peak of the Cu(OH)2 substance, and the peak value of the characteristic peak of the sample with a time of 800s is the highest.
[0034] Example 3
[0035] This embodiment provides an experimental method for rapidly preparing copper oxide nanowires by controlling the annealing temperature, which specifically includes the following steps: Step 1: vertically place the Cu(OH)2 mesh prepared by constant voltage anodization at 1.4 V for 800 s in a quartz crucible, and place the quartz crucible containing the Cu(OH)2 mesh in a tube furnace; Step 2: Heat treatment is performed in an argon atmosphere at a temperature of 200-600°C, a heating rate of 2°C / min, and a holding time of 2 hours. After high temperature annealing, Cu x O nanowires.
[0036] Figure 1 This is a flow chart of the experimental method for rapidly preparing copper oxide nanowires according to the present invention. This embodiment can correspond to all the links in the flow chart. Figure 4 The Cu prepared at 200°C (a), 300°C (b), 400°C (c), 500°C (d), 550°C (e), and 600°C (f) in Example 3 of the present invention is x Optical microscope image (sub-image) and scanning electron microscope image (main image) of O nanowire material, where the scanning electron microscope was taken at a magnification of 25000× Figure 2 g. Figure 2 h. Figure 2 i, corresponding to Figure 2 d. Figure 2 e. Figure 2 f Cu(OH)2 nanowire material photographed at a magnification of 10000×. Comparison of experimental conditions at different annealing temperatures. Cu annealed at 550℃ x O The nanowire tips are intact, the nanowires are long and densely distributed. Figure 5 The Cu prepared in Example 3 of the present invention at different annealing temperatures is shown in FIG. x From the Raman curve (e) and X-ray diffraction curve (f) of O nanowire materials, we can find the characteristic peaks of CuO and Cu2O substances. The peak value of the characteristic peak of the sample annealed at 550℃ is the highest.
[0037] Example 4
[0038] This embodiment provides a Cu x The method of photoelectrochemical testing and application testing of O nanowires specifically includes the following steps: Step 1: Prepare a test solution of Na2SO4 with a concentration of 0.1 mol / L and deoxygenate the electrolyte by bubbling dry nitrogen for at least 30 minutes; Step 2: Select the sample prepared in Example 3 and cut it into Cu sheets with a size of 1 cm × 1 cm. x O network, Cu in the three-electrode electrochemical reaction device x O mesh was used as the working electrode, Pt sheet as the counter electrode, AgCl electrode as the reference electrode, and Cu was tested under xenon lamp irradiation. x The photocurrent of the O nanowire, where the time interval between switching the xenon lamp on and off is 50 s; Step 3: Select the sample prepared in Example 3 and cut it into Cu sheets with a size of 1 cm × 1 cm. x O network, the UV-visible absorption of the material was tested in the wavelength range of 200nm to 800nm, and the Cu annealing temperature of 550℃ was calculated. x Tauc curve of O nanowire; Step 4: Select the sample prepared under the annealing temperature of 550°C in Example 3 and cut it into Cu sheets with a size of 1 cm×1 cm. x O network, Cu in the three-electrode electrochemical reaction device x O mesh was used as the working electrode, Pt sheet as the counter electrode, and AgCl electrode as the reference electrode to test Cu x O Photomott-Schottky curves of nanowires; Step 5: Prepare an electrolyte with a concentration of 0.1 mol / L Na2SO4, and introduce dry nitrogen gas for bubbling for at least 30 minutes to deoxidize the electrolyte. Select the samples prepared under the annealing temperatures of 500°C, 550°C, and 600°C in Example 3, and cut them into Cu sheets with a size of 1 cm×1 cm. x O net, using H-type electrolyzer to collect hydrogen and oxygen, Cu x O mesh was used as the working electrode, Pt sheet as the counter electrode, AgCl electrode as the reference electrode, and an external voltage between -0.6 V and -0.8 V was applied under xenon lamp irradiation. x O nanowire material produces hydrogen on one side, where a proton exchange membrane is used in the middle of the H-type electrolyzer to separate the hydrogen and oxygen solutions, and rhodamine B (Rh B) is added to one side of the Pt sheet for electrochemical degradation while Cu x Photoelectrochemical hydrogen production on one side of the O network; Step 6: Select the sample prepared under the annealing temperature of 550°C in Example 3 and cut it into a circular Cu x O mesh is used as the positive electrode material, Li sheet is used as the negative electrode, and 1cm is reserved for the positive electrode shell of the battery. 2 The circular hole allows the xenon lamp to directly illuminate the Cu xO material surface, the Li-CO2 battery was placed in a sealed gas chamber of 0.03MPa pure CO2, and the discharge voltage of the light-assisted Li-CO2 battery was tested under discharge conditions, where the time interval between switching the xenon lamp was 100s; Step 7: Select the sample prepared under the annealing temperature of 550°C in Example 3 and cut it into a circular Cu x O mesh is used as the positive electrode material, Li sheet is used as the negative electrode, and 1cm is reserved for the positive electrode shell of the battery. 2 The circular hole allows the xenon lamp to directly illuminate the Cu x O material surface, the Li-CO2 battery was placed in a closed gas chamber of 0.03MPa pure CO2, and the cycle performance of the light-assisted Li-CO2 battery was tested under the condition of continuous irradiation of a xenon lamp, where the constant current charge and discharge current was 0.01mA and the charge and discharge time was 1h.
[0039] Figure 6 This is a photoelectrochemical test and application test diagram in Example 4 of the present invention, such as Figure 6 aCu x From the photocurrent curve of the O nanowire material, it can be found that the photocurrent of the sample prepared under the annealing temperature of 550°C in Example 3 is the largest; Figure 6 aCu x The UV-visible absorption curve of the O nanowire material shows that the sample prepared under the annealing temperature of 550°C in Example 3 has the largest absorption intensity. The Tauc curve of the sample is plotted (eg Figure 6 c) and the Mott-Schottky curve (as Figure 6 d), through the arrangement and calculation of experimental data, the Cu x Schematic diagram of the energy band of O nanowires (such as Figure 6 e). For the application of photoelectric water decomposition to produce hydrogen, Figure 6 f shows the hydrogen production effect diagram, it can be found that adding rhodamine B (Rh B) on one side of the Pt sheet for electrochemical degradation can effectively promote the Cu x The photoelectrochemical hydrogen production on one side of the O network is carried out, and the sample prepared under the annealing temperature of 550°C in Example 3 has the best hydrogen production effect. Figure 6 g and Figure 6 f, the photocurrent and dark current curves and charge-discharge cycle curves of the light-assisted Li-CO2 battery all tested charge-discharge voltages close to the theoretical values, proving that Cu x O nanowire materials solve the problem of low light energy utilization and are beneficial to the separation of photogenerated electrons and hole pairs.
[0040] Summary: The present invention relates to the field of photoelectrocatalytic material preparation and photoelectrochemical technology of energy and environment, and in particular to an experimental method for rapidly preparing copper oxide nanowires and its application. The application of copper oxide nanowire materials in light-assisted Li-CO2 batteries is a good solution to energy and environmental problems. x O substrate, Cu was prepared by anodic oxidation and high temperature heat treatment x O nanowire arrays, because each copper wire has a cylindrical three-dimensional structure, have better performance than Cu prepared from traditional copper sheets and copper foils. x O nanowires have a higher specific surface area, which allows more nanowires to grow on a limited substrate space, and helps to expose them to more light in optoelectronic testing and applications. Through constant voltage anodization, a Cu(OH)2 nanowire array is quickly prepared on the surface of a copper mesh, which solves the problem that the surface current deviation caused by the error in the surface area of the material during the anodization of the copper mesh makes it difficult to maintain a consistent structure of the nanowires. The morphological characteristics are better than those of the nanowires currently prepared by constant current anodization. This method can be used to complete the anodization of larger areas of materials. The preparation process is simple and convenient, and the preparation cost is low, which is conducive to industrial production. Through high-temperature heat treatment, Cu(OH)2 is quickly dehydrated to prepare Cu in situ x O nanowire arrays, this in-situ growth technology helps to maintain good contact and adhesion between the nanowires and the substrate, the copper mesh substrate is used as a current collector, no additional conductive agent and adhesive are required, and relatively excellent battery performance can be guaranteed, so that as a positive electrode material for Li-CO2 batteries, the charge and discharge voltage close to the theoretical value is obtained. x O nanowire materials have a wide visible light absorption range as photoelectrocatalytic materials, and also have good hydrogen production performance in photodecomposition of water to produce hydrogen. In addition, they can effectively promote Cu ions to produce hydrogen while performing electrochemical degradation on the oxygen production side. x Photoelectrochemical hydrogen production on one side of the O network generates clean energy while degrading pollutants, which is also a new idea for solving energy and environmental problems.
[0041] Although the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as limiting the present invention.
Claims
1. An experimental method for rapidly preparing copper oxide nanowires and its application, characterized in that: The steps include: Step 1: Using deionized water as solvent, adding KOH and continuously stirring to obtain an electrolyte for an anodic oxidation reaction, and introducing dry nitrogen to deoxygenate the electrolyte; Step 2: Cut out copper meshes and copper sheets of the same size, first degrease them in a mixed solution of NaOH and NaHCO3, then prepare a polishing solution in the ratio of HF:HNO3:H2O=1:4:5 (vol%), polish the degreased copper meshes and copper sheets for 20-30 seconds, and place them in a water washing solution prepared in the ratio of C2H5OH:C3H6O:H2O=1:1:10 (vol%) for ultrasonic washing for about 10 minutes, and then use compressed air to dry the copper meshes and copper sheets to remove organic pollutants and oxide layers on the surfaces of the copper meshes and copper sheets; Step 3: In the electrochemical reaction device of the double-electrode system, a copper mesh and a copper sheet are used as the anode and cathode, respectively. The copper mesh is electrochemically anodized at a constant voltage, and the temperature range of the electrochemical reaction device is controlled between 20 and 30°C using a rotary evaporation table. A Cu(OH)2 nanowire array is quickly prepared on the surface of the copper mesh. The Cu(OH)2 mesh after constant voltage anodization is rinsed with deionized water and then dried using a compressed air stream; Step 4: Place the Cu(OH)2 mesh vertically in a quartz crucible in a tube furnace and perform heat treatment under an argon atmosphere. After high temperature annealing, the Cu x O nanowires; Step 5: Prepare a test solution of Na2SO4 with a concentration of 0.1 mol / L, deoxygenate the solution with dry nitrogen, and x O mesh was used as the working electrode, Pt sheet as the counter electrode, and AgCl electrode as the reference electrode. The photoelectrochemical properties of the materials were tested under xenon lamp irradiation. The Cu with the largest photocurrent was selected. x O network is used in photolysis of water to produce hydrogen and light-assisted Li-CO2 battery.
2. The experimental method for rapidly preparing copper oxide nanowires and its application according to claim 1, characterized in that: The electrolyte for the anodic oxidation reaction in step 1 is a KOH solution with a concentration of 2 mol / L, and dry nitrogen is bubbled in for at least 30 minutes.
3. The experimental method for rapidly preparing copper oxide nanowires and its application according to claim 1, characterized in that: The mixed solution for degreasing treatment in step 2 is a mixed solution of NaOH and NaHCO3 with a concentration of 1 mol / L, and the degreasing time is 300 to 600 seconds.
4. The experimental method for rapidly preparing copper oxide nanowires and its application according to claim 1, characterized in that: In step 3, the copper mesh is electrochemically anodized at a constant voltage in the range of 1.2 to 1.7 V, and the reaction time is 200 to 1200 seconds.
5. The experimental method for rapidly preparing copper oxide nanowires and its application according to claim 1, characterized in that: In step 4, the heat treatment is performed in an argon atmosphere at a temperature of 200-600° C., a heating rate of 2° C. / min, and a holding time of 2 hours.
6. The experimental method for rapidly preparing copper oxide nanowires and its application according to claim 1, characterized in that: Application of copper oxide nanowire material in step 5 in light-assisted Li-CO2 battery.
Citation Information
Patent Citations
Foam copper-supported porous copper oxide nanowire composite material and preparation method and application thereof
CN106629813A
Nano-porous copper-loaded shape-controlled copper-based oxide composite as well as preparation method and application thereof
CN108597892A
Foamy copper in-situ growth copper oxide / cuprous oxide photocatalytic material as well as preparation method and application thereof
CN113546624A
Cited By
Intelligent production process of magnesium deposition hydrogen storage material
CN120308912A
An intelligent production process for magnesium deposition hydrogen storage materials
CN120308912B